Production of hydrogen from methanol steam reforming over CuO-ZnO-Al2O3 catalyst a plant design - Arteta, Allen O. Jr.; Herrera, Jose Vergel T.; Mercado, Charlemagne L.; Dela Cruz, John Von Wernher C. (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
The feasibility of a hydrogen and carbon dioxide (as by-product) production plant utilizing a methanol steam reforming process was studied. Being cheaper by roughly 55% than the conventional water electrolysis method in the Philippines, the proposed process allowed the project to dominate the 79.5 thousand metric ton Philippine hydrogen market. The facility, located near JG Summit at Simlong, Batangas, was set to produce 1,320 Sm3 per hour of hydrogen gas, with 99.99% purity, and 430 Sm3 per hour of carbon dioxide, with 95% purity. The plant process was divided into four parts, namely (1) raw material storage, for methanol and demineralized water storage, (2) methanol-steam reforming, for methanol dehydrogenation, (3) hydrogen purification and storage, for hydrogen purification using a pressure-swing adsorption unit, and (4) carbon dioxide purification and storage, where a pressure-swing adsorption unit was also utilized. With an FCI of USD 53.77 million and an operation span of twenty years after two years of construction, the plant yielded an IRR of 13.94% which is below the desired 20% as prescribed by Timmerhaus, payback period of 10.7 years which exceeds the conventional target of 5 years for gas companies, and an NPV of about USD 58.0 million. It is concluded that the methanol steam reforming process is technically feasible. Looking into other ways of storing hydrogen to possibly reduce the storage cost is greatly recommended. Other copper-based catalysts as well as utility optimization may also be explored.
Submitted in partial fulfillment of the requirements in ChE 142 Chemical Engineering Plant Design.
Keywords: Hydrogen; Chemical plants -- Design and construction